The Correlation between Vocabulary Knowledge and English Language Proficiency at Undergraduate Level - Rafique, Samia; Waqas, Ali; Shahid, Choudhry (Pakistan Journal of Humanities and Social Sciences, 2023)
The primary objective of this study is to investigate the relationship between undergraduate English language students' vocabulary knowledge and language proficiency. The population of the study was the English department students at the University of Lahore. The sample was taken from the fifth to eighth semesters using cluster sampling. Through a vocabulary test, the size of the productive vocabulary, the size of the receptive vocabulary, and the depth of knowledge of the vocabulary were all found to significantly correlate with speaking performance. In multiple regression analyses, vocabulary knowledge was found to be the cause of 26% of the variance in speaking proficiency. The sig. (two-tailed) coefficient of the relationship between the two factors, and a correlation coefficient R value of 0.784 at the 0.05 level of significance was deemed strong. It expected that there was a strong positive connection between the vocabulary information and understudies language capability. The regression explains a consolidated effect of vocabulary knowledge on students' language proficiency. Vocabulary knowledge is positively correlated with language proficiency, according to the findings. Pedagogical implications and suggestions for future research are presented on the basis of the findings of the study.